2019
DOI: 10.29271/jcpsp.2019.05.410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flap Fixation Technique in Modified Radical Mastectomy on Incidence of Postoperative Seroma Formation

Abstract: Objective: To determine the efficacy of flap fixation technique on formation of postoperative seroma after modified radical mastectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…This also agrees with Kontos et al (11) and Schuijtvlot et al (12) . However, this disagrees with Najeeb et al (3) who found that after modified radical mastectomy, there is no substantial reduction in the frequency of seroma development due to flap fixation.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This also agrees with Kontos et al (11) and Schuijtvlot et al (12) . However, this disagrees with Najeeb et al (3) who found that after modified radical mastectomy, there is no substantial reduction in the frequency of seroma development due to flap fixation.…”
Section: Discussionmentioning
confidence: 58%
“…The most prevalent early consequence in MRM patients is seroma formation (2) . Seroma is a sterile clear fluid collection, which developed in the space between the chest wall and skin flaps following MRM (3) .…”
Section: Introductionmentioning
confidence: 99%
“…The total study population consisted of 2,956 individuals divided into a study group (SG) that included 1,418 participants (48%) and a control group (CG) that included 1,538 participants (52%). Fifteen studies (Almond et al, 2010; Arafa et al, 2019; Awad et al, 2020; Huang et al, 2021; Khater et al, 2015; Mazouni et al, 2015; Myint et al, 2020; Najeeb et al, 2019; Ouldamer et al, 2015; Sakkary, 2012; ten Wolde et al, 2014; van Bastelaar et al, 2016; van Zeelst et al, 2022; Vettuparambil & Subramanya, 2021; Wu et al, 2020) used quilting sutures as the procedure of choice for flap fixation, three studies used a surgical adhesive (Eichler et al, 2016; Ohlinger et al, 2018; van Bastelaar et al, 2017), and one researcher used both quilting sutures and a surgical adhesive (de Rooij et al, 2021). See Table 1 for detailed information about each of the studies included in the systematic review and meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The general characteristics of the 8 eligible trials are shown in Table 1 (Ref. [8][9][10][15][16][17][18][19]). For the Granzier, R. W. Y study [10], it involved three groups.…”
Section: Searching Resultsmentioning
confidence: 99%
“…Including flap quilting, several surgical techniques have been used to obliterate the dead space [6]. However, based on the existing data of several trials [7][8][9][10][11][12][13][14][15][16][17][18][19], there are conflicting results in the effectiveness at reducing the incidence of seroma.…”
Section: Introductionmentioning
confidence: 99%